Measurement of area difference ratio of Photoplethysmographic pulse wave in patients with pre-eclampsia - Ying Feng; Dan Drzymalski; Baihui Zhao; Xuan Wang; Xinzhong Chen (BMC, 2018)
Abstract Background Preeclampsia (PE) is associated with an increase in maternal arterial stiffness, which may be reflected by photoplethysmography (PPG) of the pulse wave. The aim of this study was to investigate area difference ratio (ADR), a novel parameter derived from PPG, in women with and without preeclampsia. Methods Patients with and without preeclampsia in the third trimester were enrolled. All patients had photoplethysmography of the pulse wave assessed. ADR was compared between the two groups. Results Seventy-two patients in the third trimester of gestation, of which 36 had preeclampsia and 36 did not, were enrolled. The ADR was lower in the preeclampsia group vs. the non-preeclampsia group (0.725 [IQR 0.681-0.779] vs. 0.752 [IQR 0.717-0.910], P < 0.01). Conclusions Measuring the ADR through analyzing PPG of the pulse wave may be a useful diagnostic tool in patients with preeclampsia.